(untitled) (Revista Sapiência: sociedade, saberes e práticas educacionais (2238-3565), 2020)
Urbanization changes the structure and composition of the environment, altering the quality and quantity of resources provided by it, thus affecting the richness and composition of birds. In this study, we investigated the relation of the bird communities and bird trophic guilds with a gradient of plant structure in an urban area, in the southern Goiás state, Brazil. We surveyed bird communities in ten city squares of Quirinópolis, between months March and October 2013. We found 62 bird species distributed in 24 families, being omnivores (n = 20 spp.) and insectivores (n = 18 spp.) comprised the most richness trophic guilds. For plant structure, we found 754 plant individuals, distributed in 17 families with 37 species. Bird composition and the richness of frugivorous species were relationship with the gradient of plant richness in city squares. While, the abundance of omnivorous and granivorous species were related by the gradient of plant abundance. We conclude that different aspect of vegetation structure are essential to harbor a rich and diverse bird community in city squares. We highlighted that programs of afforestation should consider the diversity of plant species. Key words: Urban area. Trophic guilds. Bird composition. Species richness.